A transição do quinto para o sexto ano do Ensino Fundamental sob a perspectiva dos alunos: uma proposta de intervenção - Ijano, Andréa Soriani (2019)
The following research aimed at identifying expectations and difficulties faced by students during the transition from fifth to sixth grade at a private school located in the West Area of São Paulo. Based on the data obtained, we also aspired to creating an action plan, alongside the school’s pedagogical staff, in order to diminish the problems pointed out by the students. Specific objectives aimed at discovering possible causes for the difficulties mentioned by the students, as well as identifying significant ways these were helped during this transition period. Initially, we have proceeded with bibliographic research using the keywords “transition fifth to sixth grade”, “elementary school discontinuity”, “transition fifth to sixth grade expectations”. The data shown by this preliminary search have revealed the existence of few studies about this issue, which reaffirmed the observation of a discontinuity between fifth and sixth grades. We have worked on giving expression to the students engaged in this process, considering the existing papers on this matter mostly present teachers and coordinators as research subjects. After brief historic contextualization of Brazilian Elementary School, pinpointing information about the final years of primary school and with theoretical support based on the reflexions of researchers such as Dias-da-Silva (1997), Prati (2005), Hauser (2007), Davis et al (2012), Bôas (2014) and Borges (2015), who have developed research in these areas, we have presented the content of the data obtained for this qualitative research. For that matter, we have applied open questionnaires for two fifth-grade groups (a total of thirty-six students) and, subsequently, we have promoted two discussion groups with sixth-and-seventh-grade students aiming at discovering whether the expectations presented by the fifth-grade students were accomplished, the challenges they have faced, how they felt and which kind of support they had and from whom, during the same period of their lives. Data analysis has shown that, even for students who were used to having multiple teachers since fifth grade and we said to feel prepared, the transition to sixth grade brings anxiety towards the number of different teachers and a concern towards the new school routine. It is a necessity for students to feel confident about the new routine and how they will be received by the new teachers. Therefore, such aspects have cooperated for the development of a deeper understanding about the issues behind this transition, and for the collective elaboration of an action plan aimed at diminishing such difficulties presented by students in this period